DEVELOPING CHARACTER BASED INTERACTIVE LEARNING MEDIA TO FACILITATE STUDENTâS SELF-LEARNING OF CAPITA SELECTA MATHEMATICS (A RESEARCH ON MATHEMATICAL CRITICAL AND CREATIVE THINKING SKILLSOF MATHEMATICS DEPARTEMENT STUDENTOF TEACHER TRAININGAND EDUCATION FACULTY OF SILIWANGI UNIVERSITY IN TASIKMALAYA) - PATMAWATI, HETTY; RATNANINGSIH, NANI; HERMANTO, REDI (Sriwijaya University Learning and Education International Conference, 2016)
The objectives of this research are to design and develop character-based Interactive learning media to facilitate autonomous learning of college students in the course Capita Selecta to develop critical and creative thinking mathematical skills. Research methods and properties of the beginning of the study in the first phase of theoretical studies, mainly carried out in the literature study and consideration of the rational, empirical studies conducted when testing teaching materials and instruments interactive critical and creative thinking skills mathematically. The sample in this research is mathematics education students who take courses capita selecta math 3 group are 110 people. Data are collected to measure the ability to think critically and mathematicallycreative through a written test, while learning autonomy used to measure Questionnaire with Likert scale. The Results of the Research is that a character-based interactive learning media facilitate self-learning in the course Capita Selecta. The ability to think critically and mathematically creative of Students are adjusted at a high level qualifications. The Highest error of mathematic critical thinking made by students are at the focus indicator while the highest error of mathematic creative thinking are at the originality indicator.